Sodium-glucose co-transporter-2 (SGLT2) inhibitors: comparing trial and real world use (study protocol) - McGovern, A; Feher, M; Munro, N; De Lusignan, S (Springer, 2017)
Sodium-glucose co-transporter-2 (SGLT2) inhibitors (gliflozins) are the newest class of medication available to treat type 2 diabetes (T2DM). Recent findings from the first complete cardiovascular safety trial in SGLT2 inhibitors, the Empagliflozin, Cardiovascular Outcomes, and Mortality in type 2 diabetes (EMPA-REG OUTCOMES) trial, demonstrated reduced cardiovascular outcomes in people with high cardiovascular risk. How to apply these findings to clinical practice remains unclear, with questions remaining on who will reap this cardiovascular benefit.To describe the proportion of people in the real world currently treated with SGLT2 inhibitors who meet the inclusion criteria of the EMPA-REG trial and therefore could expect the cardiovascular benefit identified by the trial. Similarly, to describe the proportion of people from the whole T2DM population who could also expect this same benefit.Routinely collected data from UK primary care in the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) database will be used. The study population will include all people with T2DM within this database (approximately 60,000). We will perform a cross-sectional investigation to describe the characteristics of people currently using SGTL2 inhibitors compared with the population of the EMPA-REG trail. We will similarly compare the characteristics of the RCGP RSC T2DM cohort with the inclusion criteria of the EMPA-REG trial.People with T2DM using a pre-existing verified clinical ontological process will be identified, as will people with prescriptions for SGLT2 inhibitors and other medications using Read coded and other proprietary coding systems. Descriptive statistics will be used to characterise the key clinical characteristics of people with T2DM using SGLT2 inhibitors and to compare these characteristics to people included in EMPA-REG trial; the proportion of people who match the trial criteria will be reported.Peer review publication reporting the real world lessons for clinical practice.AstraZeneca.